Custo logístico de distribuição em uma empresa de polpa de frutas: uma análise entre frota própria e terceirizada - Sá, Pedro Passador Bittencourt de (2020)
In Brazil, the food industries were responsible for 9.6% of PIB in 2019. However, in this scenario, the companies producing fruit pulp had the worst growth rates, with a fall of 4.1%. Associated with this, studies related to business logistical costs have gained prominence as a way of guaranteeing the success or failure of organizations. Considering that within the logistical costs, the distribution is the one that has the most financial impact, the identification of these costs helps in making managerial decisions in order to optimize the product distribution process. Thus, this work aimed to calculate the logistical distribution costs of a small fruit pulp company that uses its own fleet to carry out the distribution in order to analyze whether it would be more advantageous to maintain its own fleet or to outsource it. Within this objective, specific objectives were set: to calculate the distribution costs by state of operation of the company; calculate the total distribution costs of the industry; raise quotation from a third-party distribution company; analyze the two fleet models (own and outsourced) and indicate which one best suits the current situation of the industry. To achieve the proposed objectives, we used the case study method with a quali-quantitative approach. The result of the research revealed that financially the own fleet has lower costs in relation to the outsourced. However, the benefits presented by outsourcing add quality and agility to the distribution process in relation to the company's own fleet. In making decisions, therefore, these two considerations must be taken into account, so that the result is one that adds more benefits to the entire logistical distribution process.